F = = dt d mu dt √1-u²/c² m / T = ²^U2² / 0² {² - a + = m u(u. a) (c²-u²) du dt √1-u²/c² }. qed + u (-12) dt -2u. du (1-u²/c²)3/2
F = = dt d mu dt √1-u²/c² m / T = ²^U2² / 0² {² - a + = m u(u. a) (c²-u²) du dt √1-u²/c² }. qed + u (-12) dt -2u. du (1-u²/c²)3/2
Related questions
Question
I need to check whole steps of this answer, thanks
![F
=
dp
d
mu
dt dt √1-u²/c²
=
M
√1-u²/c²
{
a +
du
dt
m
u
= ({ √ ₁ - ³ / + " ( - )
√1-u²/c²
₁
(1 -- u²/c²)³/2
u(u.a)
qed
(c²-u²
21. du
dt
42) }](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2F6b164c93-b180-40d7-aeb8-dca73ab45463%2F4a6b5268-7b0a-4e73-acbe-295b272ebaf2%2F61spwtq_processed.png&w=3840&q=75)
Transcribed Image Text:F
=
dp
d
mu
dt dt √1-u²/c²
=
M
√1-u²/c²
{
a +
du
dt
m
u
= ({ √ ₁ - ³ / + " ( - )
√1-u²/c²
₁
(1 -- u²/c²)³/2
u(u.a)
qed
(c²-u²
21. du
dt
42) }
Expert Solution
![](/static/compass_v2/shared-icons/check-mark.png)
This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
Step by step
Solved in 2 steps with 1 images
![Blurred answer](/static/compass_v2/solution-images/blurred-answer.jpg)